0498 TITLE: Simmons Chin Press and Tongue Curl (SCPTC) Maneuver is a Reproducible Objective Physical Exam Finding to Screen for Obstructive Sleep Apnea (OSA) Associated with Cardiovascular Morbidities and All-Cause Mortality. (27th April 2018) - Meskill, G J; Kincheloe, K; Simmons, J H; Meskill, S D
Abstract: Introduction: Moderate-to-severe obstructive sleep apnea (OSA) is a condition that afflicts at least 6% of US adults with 80% of such cases currently undiagnosed. There is a significant risk of long-term cardiovascular morbidity and mortality if untreated, with an all-cause mortality odds ratio (OR) of 1.17 for AHI > 15 and 1.46 for AHI > 30, and a stroke OR of 2.86 in men with AHI > 19. The Simmons chin press and tongue curl maneuver (SCPTC) is an objective physical exam feature used to assess the collapsibility of the upper airway (https://youtu.be/liTQH9eYhCo ). To date, there is little published data on the ability of the SCPTC to predict OSA. Methods: A retrospective cohort of 332 consecutive new patients from 2/8/2017–9/1/2017 was identified. Patients were excluded for age < 18 (n = 19), missing documentation of ENT exam features (n = 75), studies performed using oral appliance (n = 3), or inability to tolerate SCPTC maneuver (n = 4). 231 charts were reviewed. The chin press and tongue curl are each scaled 0 to 2 and these results were summed for a total of 4 points. This score was divided into high (3–4 points) vs low (0–2 points). AHI ≥ 15 was considered reference standard for diagnosis of moderate-to-severe OSA. Data was entered into a standard 2 x 2 table (Stata). Results: Patients with high summed SCPTC score had an odds ratio for moderate-to-severe OSA of 2.7 (CI 1.478–4.930, p = 0.001) with a sensitivity of 72%. Conclusion: The SCPTC is an easy, reproducible, and objective physical exam finding that can be used to screen for forms of OSA known to increase cardiovascular and all-cause mortality risk. Support (If Any): N/A.